IMPROVEMENT OF RAILWAY RIDE INDEX THROUGH PITCH MOTION WITH CONSIDERATION OF LONGITUDINAL DAMPERS - Abdullah, Mohd Azman; Ibrahim, M.; Jamil, F. Mohamed; Harun, M. H.; Ahmad, F.; Hendrowati, Wiwiek (Journal of Engineering and Technology (JET), 2025)
Longitudinal dampers also known as yaw dampers play a crucial role in enhancing the ride comfort of railway vehicles by mitigating longitudinal vibrations, which can significantly impact passenger comfort and safety. This study investigates the enhancement of railway ride comfort by focusing on pitch motion control through the implementation of longitudinal dampers. The research aims to address the significant impact of longitudinal vibrations on passenger comfort, which are often exacerbated by track irregularities, braking, and acceleration forces. By integrating longitudinal dampers into the suspension system, the study proposes a method to mitigate these vibrations and improve the overall ride quality. A comprehensive dynamic model of a railway vehicle is developed, incorporating the effects of longitudinal dampers on pitch motion. The model was previously validated through both simulations and real-world experiments, covering a range of operating conditions and speeds. Key performance metrics, including the Sperling’s Ride Index and ISO 2631-1 standards, are used to evaluate the effectiveness of the proposed system. With 1.2 weighted primary longitudinal damper, the ride index is improved from 1.21 to 1.098. The results demonstrate that longitudinal dampers significantly reduce pitch-induced vibrations, leading to a marked improvement in ride comfort indices. The study also explores the practical implications of implementing longitudinal dampers, including cost, maintenance, and integration with existing railway infrastructure. The findings suggest that longitudinal dampers are a viable solution for enhancing passenger comfort in modern railway systems, providing a smoother and more stable ride experience. This research contributes to the field of railway engineering by offering a novel approach to ride comfort improvement, emphasizing the importance of addressing longitudinal vibrations through advanced suspension technologies.